TRANSFORMATION OF FINANCIAL PROVISION OF LABOR POTENTIAL THROUGH THE LENS OF HEALTH SYSTEM REFORM - Tsizhma Yu.І.; Tsizhma, O.A. (The actual problems of regional economy development, 2019)
The article is devoted to the study of the state of financial resources of the health care sector and the regeneration of financial security approaches for the purpose of developing labor potential. Generalizations of approaches of financial support of the health care sphere with the purpose of development of the labor potential of the state. The necessity of reforming the health care system of Ukraine is considered, because in terms of health care expenditures our country is by far not high in the overall world ranking. The question of the share of public resources in health care financing in Ukraine has been investigated. The budgetary model of health care organization and financing is analyzed, which has inherited our state and is now being transformed into a system that combines public and private sources of financing. It is determined that fundamental changes in health financing approaches should be aimed primarily at ensuring harmonious development, high efficiency and active longevity of citizens, eliminating risk factors for public health, improving the quality of life of the population, and as a result, preserving and restoring the country's labor potential. Considering that the health care system of any country is affected by many socio-economic, political, cultural, historical and other factors, it is determined that they are determining the cost of health care as a percentage of GDP, the amount of real health expenditures per capita, the share of public expenditures in the structure of total health expenditures. For the successful political, social and economic development of the work potential of human health, it is considered as the main factor and result and is a component of human well-being. The research focused on the need to fulfill the state's legal obligation to implement social health insurance, as a guarantee of the exercise of citizens' rights in health and medical care, and to continue the reform of the primary care delivery unit. It should be remembered that the greatest progress in addressing the issue of health promotion has been achieved by those countries that have introduced a health insurance mechanism in the health care system. The approaches to improving the financial security of the health care system in the context of existing problems are highlighted.